Rural Latino Immigrant Caregivers’ Conceptions of Their Children’s Oral Disease - Sarah Horton, PhD; Judith C. Barker, PhD (Blackwell Synergy, 2008)
The aim of this study was to examine Latino immigrant caregivers’ explanatory models of the causes of early childhood caries (ECC).